Bangladesh : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Bangladesh's Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria (PC). All PCs at end-December 2013 (the test date for the fourth review) were met, and all structural benchmarks have been completed. Fiscal and monetary policies are set to retain a prudent stance to safeguard macroeconomic stability. Based on strong program performance to date and the policy framework going forward, the IMF staff recommends completion of the review, as well as modification of PCs for end-June 2014 on account of reserve over-performance.